Turbine Performance of Variable Geometry Turbocharger Applied to Small Gasoline Engine Considering Heat Transfer Effect - Jeong-Eui Yun; Joon-Young Shin; Cartur Harsito; Gi-Yong Kim; Hyung-Jun Kim (Energies)
The performance of the turbine in a variable geometry turbocharger (VGT) may be affected by changes in the vane operating angle and heat transfer loss during operation. However, existing studies have been conducted under the assumption of an adiabatic process. In this study, we investigated the effect of heat transfer between all working fluids and a VGT structure when using computational fluid dynamics to evaluate turbine performance. Through this study, we confirmed that when heat transfer was considered, the turbine efficiency decreased by approximately 2–6%, depending on the vane position angle change, compared to when heat transfer was not considered. In addition, the total entropy production ratio, which represented the flow loss in the turbine during operation, increased by approximately 0.2–0.5% when heat transfer was considered. In conclusion, the findings confirmed that the heat transfer phenomenon directly affected the efficiency and flow loss during the turbine performance evaluation process.